ANALISIS EFEKTIVITAS MESIN PRODUKSI PULSE TUBE FILTER PADA PROSES PENGOLAHAN FATTY ACID HYDROGENATION DENGAN MENGGUNAKAN METODE OVERAL EQUIPMENT EFFECTIVENESS (OEE) - Delta Eprynci Tarigan; Masdania Zurairah; M. Fiza Lubis (Sekolah Tinggi Pariwisata Mataram, 2023)
Research has been carried out on the causes of failure of pulse tube filter production machines). The six big losses factor that has the greatest percentage of influence on losses time and needs to be repaired at reduced speed losses is equal to 41.66%, idling/minor stopage losses of 25.14% means the low performance efficiency of the pulse tube filter machine is caused by high failure that occurs thus affecting the level of effectiveness of the machine.